2014
DOI: 10.1186/1471-2458-14-292
|View full text |Cite
|
Sign up to set email alerts
|

Do low-income neighbourhoods have the least green space? A cross-sectional study of Australia’s most populous cities

Abstract: BackgroundAn inequitable distribution of parks and other ‘green spaces’ could exacerbate health inequalities if people on lower incomes, who are already at greater risk of preventable diseases, have poorer access.MethodsThe availability of green space within 1 kilometre of a Statistical Area 1 (SA1) was linked to data from the 2011 Australian census for Sydney (n = 4.6 M residents); Melbourne (n = 4.2 M); Brisbane (n = 2.2 M); Perth (n = 1.8 M); and Adelaide (n = 1.3 M). Socioeconomic circumstances were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(179 citation statements)
references
References 58 publications
9
164
4
2
Order By: Relevance
“…Increasingly, research is finding that biophilic tendencies are significant contributors to reaching emotional and psychological wellbeing [6,18,29,50]. Interacting with nature can result in a range of human benefits including physical health, mental health, psychological health, psychological wellbeing, life meaning, cognitive ability and social cohesion, and provide spaces for physical and social activities to take place [3,14,18,19,25,28,[50][51][52][53][54].…”
Section: Food Related Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, research is finding that biophilic tendencies are significant contributors to reaching emotional and psychological wellbeing [6,18,29,50]. Interacting with nature can result in a range of human benefits including physical health, mental health, psychological health, psychological wellbeing, life meaning, cognitive ability and social cohesion, and provide spaces for physical and social activities to take place [3,14,18,19,25,28,[50][51][52][53][54].…”
Section: Food Related Wellbeingmentioning
confidence: 99%
“…Suburbs of higher socio-economic advantage have significantly more overall vegetation cover, more private green cover (but slightly less public green cover), more street trees, higher plant species richness and vegetation abundance than areas of greater disadvantage [6,17,[27][28][29]. Hoffimann et al [30] found that green spaces in lower socio-economic areas raise more safety concerns, have more signs of damage, less equipment and fewer amenities (such as seating, toilets, cafes).…”
Section: Introductionmentioning
confidence: 99%
“…As it is known that green space access varies by socio-economic status, 28 and that socio-economic status is an important predictor of children's BMI, 20 it is important to properly control for any confounding effects of socio-economic status. This has been a limitation of previous research.…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…In between the two directions stands Astell-Burt et al's (2014) study on how lack of green space is linked to social inequalities in Australia's major urban areas. The study argues that inequitable distribution of parks and other 'green spaces' could exacerbate health inequalities if people on lower incomes, who are already at greater risk of preventable diseases, have poorer access [13]. In 2017, Anguluri and fellow researcher Narayanan studied the concepts of per capita urban green cover, green index for smart city planning and urban green infrastructure (UGI) and verified said concepts by using the City of Gulbarga, India, as a case study.…”
Section: Theory and Methodologymentioning
confidence: 99%